Keberhasilan TPK Pendamping Keluarga Dalam Penurunan Percepatan Stunting 2023 Di Kota Cilegon Oleh Dp3ap2kb Cilegon - Fatihah Nurul (Eastasouth Journal of Effective Community Services, 2023)
Stunting is a disruption in the growth and development of children due to chronic nutrition and recurrent infections, which is characterized by their length or height being below the standards set by the minister who handles government affairs in the health sector. Reducing stunting is an effort to reduce the number of children with stunted growth, where children experience chronic malnutrition which causes inadequate body growth. Data collection in reviewing this research, using interview and observation techniques, was carried out from September to November 2023 at the Cilegon City Women's Empowerment, Child Protection, Population Control and Family Planning (DP3AP2KB) Service, located at the address: Jl. Raya Bojonegara No. 95, Jombang Wetan, District. Jombang, Cilegon City, Banten 42411. Efforts are being made to accelerate overcoming the stunting problem in Cilegon City, namely by forming a TPK (Family Assistance Team) group, the implementation of the policy is certainly used as a guideline in realizing policy achievements. The implementation of this 5 pillar policy focuses on reducing stunting in the form of a campaign concept with a focus on understanding, behavior change, political commitment and accountability in Cilegon City, influenced by supporting factors, namely First, the existence of a regional policy which is of course used as a guideline for reducing stunting. Second, the availability of adequate human resources for implementing stunting reduction. Third, support from the Cilegon government. This implementation with a focus on understanding, behavior change, political commitment and accountability is well supported by the Cilegon government.